Atypical haemolytic uraemic syndrome as a complication of induction chemotherapy for acute lymphoblastic leukaemia. Issue 6 (27th May 2004) - Chandra, D; Lawson, S; Ramani, P
Abstract : This report describes a case of fatal haemolytic uraemic syndrome (HUS) developing in a child with acute lymphoblastic leukaemia (ALL) during induction chemotherapy. The aetiology in this case is uncertain but it may have resulted from treatment with L-asparaginase or vincristine. The possibility of HUS during induction chemotherapy for ALL should be considered early on in the treatment regimen, if clinical signs and symptoms suggest this diagnosis, so that appropriate treatment can be instituted.